Organization and Complexity of the Yak (Bos Grunniens) Immunoglobulin Loci - Wu, Mingli; Zhao, Haidong; Tang, Xiaoqin; Zhao, Wanxia; Yi, Xiaohua; Li, Qi; Sun, Xiuzhu (Frontiers in Immunology, 2022)
As important livestock in Qinghai-Tibet Plateau, yak provides meat and other necessities for Tibetans living. Plateau yak has resistance to diseases and stress, yet is nearly unknown in the structure and expression mechanism of yak immunoglobulin loci. Based on the published immunoglobulin genes of bovids (cattle, sheep and goat), the genomic organization of the yak immunoglobulin heavy chain (IgH) and immunoglobulin light chain (IgL) were described. The assemblage diversity of IgH, Igλ and Igκ in yak was similar to that in bovids, and contributes little to the antibody lineage compared with that in humans and mice. Somatic hypermutation (SHM) had a greater effect on immunoglobulin diversity in yak than in goat and sheep, and in addition to the complementarity-determining region (CDR), some loci in the framework region (FR) also showed high frequency mutations. CDR3 diversity showed that immunological lineages in yak were overwhelmingly generated through linkage diversity in IgH rearrangements. The emergence of new high-throughput sequencing technologies and the yak whole genome (2019) publication have greatly improved our understanding of the immune response in yaks. We had a more comprehensive analysis of yak immunoglobulin expression diversity by PE300, which avoided the disadvantage of missing low-frequency recombination in traditional Sanger sequencing. In summary, we described the schematic structure of the genomic organization of yak IgH loci and IgL loci. The analysis of immunoglobulin expression diversity showed that yak made up for the deficiency of V(D)J recombinant diversity by junctional diversity and CDR3 diversity. In addition, yak, like cattle, also had the same ultra-long IgH CDR3 (CDR3H), which provided more contribution to the diverse expression of yak immunoglobulin. These findings might provide a theoretical basis for disease resistance breeding and vaccine development in yak.